2017
DOI: 10.18632/aging.101282
|View full text |Cite
|
Sign up to set email alerts
|

The G-quadruplex DNA stabilizing drug pyridostatin promotes DNA damage and downregulates transcription of Brca1 in neurons

Abstract: The G-quadruplex is a non-canonical DNA secondary structure formed by four DNA strands containing multiple runs of guanines. G-quadruplexes play important roles in DNA recombination, replication, telomere maintenance, and regulation of transcription. Small molecules that stabilize the G-quadruplexes alter gene expression in cancer cells. Here, we hypothesized that the G-quadruplexes regulate transcription in neurons. We discovered that pyridostatin, a small molecule that specifically stabilizes G-quadruplex DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 54 publications
(72 reference statements)
0
61
1
Order By: Relevance
“…It has been demonstrated that the cationic porphyrin TMPyP4 and small molecule compound Pyridostatin (PDS) can bind to G-quadruplex strucures and either stabilize or destabilize them [ 17 , 66 , 67 ]. We performed CD melting experiments to determine melting temperatures (Tm) for Wt-KSHV-GQ and Wt-HCMV-GQ, respectively in the presence of TMPyP4 and PDS.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the cationic porphyrin TMPyP4 and small molecule compound Pyridostatin (PDS) can bind to G-quadruplex strucures and either stabilize or destabilize them [ 17 , 66 , 67 ]. We performed CD melting experiments to determine melting temperatures (Tm) for Wt-KSHV-GQ and Wt-HCMV-GQ, respectively in the presence of TMPyP4 and PDS.…”
Section: Resultsmentioning
confidence: 99%
“…The planar central moiety of BRACO‐19 can stack on the G‐quartet, binding through π–π interactions of the aromatic rings of the acridine and guanine molecules, while flanking groove binding arms enhance binding affinity (Burger et al, ; Sun et al, ). This overall small molecule architectural blueprint has led to a number of small molecules that have a great affinity for RNA and DNA GQs based on binding through planar stacking, intercalation and/or groove binding (Drygin et al, ; F. X. Han, Wheelhouse, & Hurley, ; H. Han, Cliff, & Hurley, ; Moruno‐Manchon et al, ). But still, very few small molecules have been found that can selectively bind to not only GQ‐based structures but selectively to the RNA product compared to the DNA.…”
Section: Targeting Rna G‐quadruplexes As a Therapeutic Approachmentioning
confidence: 99%
“…Replication in yeast is impeded at G4 motifs when the G4 DNA helicase Pif1 is disrupted [63,79,80]. G4 DNA stabilized by small molecule ligands such as pyridostatin (PDS) or PhenDC3 increase the instability at G4-forming sequences in the eukaryotic genomes indicating that the stability of G4 DNA correlates with its efficacy as replication block [81][82][83][84]. Similarly, a more problematic obstacle to replication is expected when G4 DNA is in complex with high-affinity binding protein such as the Top1 catalytic mutant (Top1Y727F), which binds to G4 DNA to form a stable complex (Figure 1, Table 1).…”
Section: Dna-protein Complexes As Dna Replication Barriersmentioning
confidence: 99%